Writing Process Approach and Its Effect on Student' Writing Anxiety and Performance - Kurniasih Kurniasih; Fitri Awaliyatus Sholihah; Atik Umamah; Ika Hidayanti (JURNAL ARBITRER, 2020)
This study aims at investigating the effect of the process approach on student writing anxiety and performance. Teachers should find ways to cope with anxiety as it is known as the negative predictor of students' writing performance. Fifteen students participated in this study. They were assigned to write an argumentative essay under the topic "Should national exam be banned?". The treatment was given following the writing stages, from outlining to publishing. SLWAI questionnaire was distributed before and after the treatment to measure the effectiveness of the process approach on students' anxiety. The findings indicated that students writing anxiety decreases from 71.27 to 63.20, which means that the anxiety level goes down from high to moderate anxiety. The second findings informed us that there is a significant difference in students writing performance after the treatment with the level of significant .000. It can be said that the writing process approach has a significant effect on students writing anxiety and performance. The pedagogical implication is also discussed.